Association between waist circumference or weight change after smoking cessation and incidence of cardiovascular disease or all-cause death in Korean adults with type 2 diabetes - Lee, Heajung; Shin, Jaeyong; Choi, Jae Woo (Frontiers in Endocrinology, 2024)
Objective To investigate the association among smoking cessation, weight or waist circumference change post-cessation, and cardiovascular disease (CVD) or all-cause death among patients with type 2 Diabetes (T2D). Materials and methods This retrospective cohort study included 32,142 patients with T2D classified according to changes in smoking status, post-cessation weight, and waist circumference. Especially for recent or long-term quitters, participants who changed from current to none/former smoker or from non-smoker to former smoker were defined as recent quitters, and those who changed from former to none/former smoker were defined as long-term quitters. CVD or all-cause death risk was evaluated. Results A total of 5,845 participants were newly diagnosed with CVD, and 3,723 died during follow-up. After adjusting for potential confounding factors, compared with current smokers, the hazard ratios (HRs) for CVD were 0.94 (95% confidence interval [CI]: 0.85–1.03), 0.82 (95% CI: 0.74–0.90), and 0.82 (95% CI: 0.75–0.90) for recent quitters, long-term quitters, non-smokers, respectively; 0.88 (95% CI: 0.78–0.99), 0.68 (95% CI: 0.57–0.81), and 0.82 (95% CI: 0.67–1.00) for long-term quitters with no waist circumference gain, long-term quitters with waist circumference gain of 0.1–5.0 cm, and long-term quitters with waist circumference gain ≥5.0 cm, respectively; and 0.79 (95% CI: 0.71–0.89), 0.85 (95% CI: 0.74–0.98), and 0.84 (95% CI: 0.60–1.17) for long-term quitters with no weight gain, long-term quitters with weight gain of 2–5 kg, and long-term quitters with weight gain ≥5 kg, respectively. Similar associations were observed for all-cause death. Conclusions Patients with T2D should maintain their weight and waist circumference after long-term smoking cessation to prevent CVD. It is more important for them to maintain weight rather than waist circumference to prevent all-cause death.